Evolving role of synthetic cytokinin 6-benzyl adenine for drought stress tolerance in soybean (Glycine max L. Merr.) - Mangena, Phetole (Frontiers in Sustainable Food Systems, 2022)
The enhanced growth and productivity of soybeans during the past decades were possible due to the application of agrichemicals such as bio-fertilizers, chemical fertilizers, and the use of high yielding, as well as disease resistant transgenic and non-transgenic varieties. Agrichemicals applied as seed primers, plant protectants and growth regulators, however, had a diminutive significance on growth and productivity improvements across the globe. The utilisation of plant growth regulators (PGRs) for vegetative growth, reproduction and yield quality improvements remains unexplored, particularly, the use of cytokinins such as 6-benzyl adenine (6-BAP) to improve soybean response to abiotic stresses. Therefore, an understanding of the role of 6-BAP in the mediation of an array of adaptive responses that provide plants with the ability to withstand abiotic stresses must be thoroughly investigated. Such mitigative effects will play a critical role in encouraging exogenous application of plant hormones like 6-BAP as a mechanism for overcoming drought stress related effects in soybean. This paper discusses the evolving role of synthetic cytokinin 6-bezyl adenine in horticulture, especially the implications of its exogenous applications in soybean to confer tolerance to drought stress.